APAKAH GENDER MASIH BERFUNGSI SEBAGAI PEMODERASI PADA FINTECH PAYMENT DALAM MASA PANDEMI COVID-19? - Dewi, Luh Gede Krisna; Latrini, Made Yenni (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.11.TAHUN.2023, 2023)
The Covid-19 pandemic has triggered many changes throughout the world. The use of financial technology (fintech) is increasing rapidly, with the millennial generation as the largest market share. The research aims to obtain empirical evidence regarding the factors that influence the actual use of fintech payments with gender as a moderating variable. The research used 400 students from various universities in Bali as respondents who use fintech payments in the modern era. The type of data used in this study is primary data, which was collected through a questionnaire using a Likert scale of 5 alternative choices. The sample selection technique uses a purposive sampling method using the Partial Least Square (PLS) approach. The results of the study found that gender strengthens the effect of perceived benefits on the sustainable use of fintech payments. Meanwhile, on the effect of perceived risk on the continued use of fintech payments, gender actually weakens the relationship. This research has implications for TAM and behavioral theory that gender differences have an influence on the level of technology adoption.